A Panel Threshold Regression Approach to Establish The FDI-Exports Linkage in Emerging Markets - Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2024)
This paper explored the impact of foreign direct investment (FDI) on exports in emerging markets using panel data ranging from 2004 to 2019. More specifically, it studied the minimum threshold level of FDI that enhances a significant exports growth in emerging markets using the static Hansen (1999)’s panel threshold approach. Existing literature agrees that FDI forms an integral component of exports growth but recently, it is clearer that FDI does not only need to be available but must exceed a certain minimum threshold point before host countries can begin to experience significant exports growth. That is the reason the author carried out this study to determine the minimum threshold level of FDI that lead to significant exports growth in emerging markets. Results show that FDI significantly improved exports in emerging markets as expected. In addition, levels of FDI equal to and above a threshold level of 2.67% of GDP led to significant exports growth in emerging markets, in agreement with more recent available literature. Such results make it prudent for emerging markets to implement policies and mechanisms that enhances FDI inflow to expand the exports base of their respective countries.